Drama, Creativity, and Critical Pedagogy - Helen Eadon-Sinkinson (PRISM)
This article focuses on the work of Paulo Freire and the social theory encapsulated within ‘Pedagogy of The Oppressed’ (1996) as applied to a professional educational context; A Year 11 GCSE drama class in preparation for their final assessment piece which was being moderated by an AQA assessor. Drama is a subject which allows for the key concepts of Freire’s theory to be explored due its creative nature. There is an explanation of how this theory has been applied in a professional context whilst drawing on the work of Boal (1992) and Nicholson (2006).